MOBIL LISTRIK âZEONâ (ZERO POLLUTION) SEBAGAI SARANA WISATA DI EKOWISATA MANGROVE WONOREJO - Syaifulah, Reza Arif; Kurniawan, Hardhani Eko; Priyohandoko, Bagus (Program Kreativitas Mahasiswa - Teknologi, 2013)
In Surabaya, Mangrove forest can be helpful for reducing the pollution beside to protect inhabitant beach from the see wave. The tour system of Mangrove forest is still use walking way and sometimes the operator use the car to deliver the tourist. It causes the air pollutions and that is not suitable for keeping the air. Zeon Electric Car can be solution as a zero pollution vehicle for Mangrove forest transportation. The advantage of this electric vehicle is no emission gas. Beside that this car uses the solar energy to charge the battery in order to get long service.